2018
DOI: 10.14306/renhyd.22.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Prácticas parentales para promover hábitos saludables de alimentación en la primera infancia en Cali, Colombia

Abstract: Introducción: Considerando la influencia del entorno familiar en el desarrollo de hábitos saludables en la primera infancia, este estudio se propuso explorar las prácticas que usan los padres para promover una alimentación saludable en niños de 1 a 5 años de la ciudad de Cali, Colombia. Materiales y métodos: Se realizó un estudio mixto con una fase cualitativa y una fase cuantitativa, con análisis secuencial. En la fase cualitativa 20 padres fueron entrevistados en profundidad. A partir de esta información se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…In our study, the fundamental role that parents have on their children’s eating habits is evident, since they decide on the selection of food, as well as on the quantity and quality provided during childhood and adolescence, as highlighted in several studies [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In our study, the fundamental role that parents have on their children’s eating habits is evident, since they decide on the selection of food, as well as on the quantity and quality provided during childhood and adolescence, as highlighted in several studies [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 85%
“…All of this may result in significant changes in the eating habits of Spanish families, particularly the low consumption of dairy products and fish and the increase in ultra-processed foods and sugars, as is also evident in other Latin American countries [ 1 ]. These eating habits require to place the focus on improving the diet of families with children aged 6 to 10 to prevent diseases, such as childhood obesity, and to develop activities for the prevention, management and control of other health problems in adulthood [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, five studies were identified by cross-referencing. Finally, 70 scientific articles were included 52–124. All these document and articles were related to 13 initiatives on physical and social environmental modifications, 7 in the area of PA and 6 with a nutrition focus (online supplemental files 2; 3).…”
Section: Resultsmentioning
confidence: 99%
“…; Alarcón C.D. 10 Prácticas parentales para promover hábitos saludables de alimentación en la primera infancia en Cali, Colombia.…”
Section: La Presencia De Latinoamérica En La Revista Española De Nutrunclassified